Use of spent yeasts from bioethanol production plant as low-cost nitrogen sources for ethanol fermentation from sweet sorghum stem juice in low-cost bioreactors - Thanawat Thanapornsin; Rattanaporn Phongsri; Lakkana Laopaiboon; Pattana Laopaiboon (Carbon Resources Conversion)
Two spent yeasts from an ethanol production plant, spent yeast after distillation (SY-AD) and spent yeast after fermentation (SY-AF), were used as low-cost nitrogen sources for ethanol fermentation from sweet sorghum stem juice (SSJ) by a commercial dry yeast (Saccharomyces cerevisiae) in air-locked flasks. SY-AF was the more effective nitrogen source for ethanol fermentation, giving ethanol concentration (PE) and ethanol productivity (QE) values of 95.22 g/L and 1.98 g/L·h, respectively. When SY-AF was disrupted by autolysis, and the spent yeast hydrolysate (SYH) obtained was used as a nitrogen supplement. It was found that ethanol production in terms of PE and QE values increased to 102.20 g/L and 2.83 g/L·h, respectively. When three bioreactors, a stirred-tank bioreactor (STR, a typical bioreactor), a column bioreactor with stirrer (CS-R, a tower bioreactor) and an external loop bioreactor (ELR, a low-cost bioreactor with no agitation), were used for ethanol production from the SSJ supplemented with SYH, the fermentation efficiencies of all bioreactors were not different. Appropriate aeration during fermentation (0.31 vvm for 12 h) in the three bioreactors could enhance the QE value, reaching 3.36 g/L·h. Both the CR-S and ELR could be successfully used for ethanol production from SSJ supplemented with SYH.